Peran Strategis LKMS dalam Pembangun Ekonomi Desa di Kabupaten Tangerang - Okviyani Pramitasari; Fizah Qudsy Aduhalim; Iman Ramadhan (STES Islamic Village, 2021)
AbstractThe empirical study of Micro Finance Institution (MFI) to investigate MFI performance in rural economics development perspective have been conducted in Java and off Java, in the early 2007 through PRA approach with group interview and individual in depth interview, involve the MFI board and customer. By using qualitative descriptive analysis approach of purposive chosen MFI, the result study obtained a following picture: (a) the existence of MFI is strategic role as intermediation of economics activities for the people who didn’t reach of conventional bank services; (b) in fact MFI services have been successful, but it was still bias of non agricultural business activities. The scheme of agricultural loan didn’t priorities, the budget of farming systemsupport relatively small. That is not more then 10 % from total of MFI budget; (c) Critical success factors of agricultural MFI development are: legality of MFI institute, management capability, seed capital support, reasonable farming system, characteristic of farming system, training of MFI management and technical guidance of customer MFI; (d) Human resource development, seed capital support and technical guidance of MFI customer are needed of the initiation and development of agricultural MFI.his Keywords: Maqashid al-Syari'ah, the concept of Islamic dwelling, the decision of Muslim consumers.